First ice thickness measurements in Tierra del Fuego at Schiaparelli Glacier, Chile - G. Gacitúa; C. Schneider; J. Arigony; I. González; I. González; R. Jaña; G. Casassa (Earth System Science Data, 2021)
Cordillera Darwin in Tierra del Fuego (Chile) remains one of the least studied glaciated regions in the world. However, this region being one of very few terrestrial sites at this latitude in the Southern Hemisphere has the potential to provide key information on the effect of climate variability and climate change on the cryosphere at sub-polar mid-latitudes of the Southern Hemisphere. Schiaparelli Glacier is located at the northern side of the Cordillera Darwin draining the north side of Monte Sarmiento (2187 m a.s.l.). Despite being one of the largest glaciers in the Cordillera Darwin, no previous in situ observation of its ice thickness had been made either at this glacier or at any other location in the Cordillera Darwin. Ice thickness is one of the fundamental parameters to understand glacier dynamics, constrain ice dynamical modelling, and predict glacier evolution. In April 2016 we performed the first successful ice thickness measurements using terrestrial ground-penetrating radar in the ablation area of Schiaparelli Glacier (Gacitúa et al., 2020, https://doi.org/10.1594/PANGAEA.919331). The measurements were made along a transect line perpendicular to the ice flow. Results show a valley-shaped bedrock with a maximum ice thickness of 324 m within a distinct glacier trough. The bedrock is located below current sea level for 51 % of the transect measurements with a minimum of −158 m, which illustrates that the local topography is subject to considerable glacier-related over-deepening.